SINBIOTIK ANTARA EKSTRAKS INULIN DARI BAWANG MERAH (Allium cepa) DENGANLactobacillus casei strain BIO 251 DAN UJI BIOAKTIVITASNYA TERHADAP BAKTERI PENYEBAB DIARE - Nunung Kurniasih Kurniasih (JURNAL ISTEK, 2012)
Inulin is prebiotic polymers mainly comprising of fructose units in wich are bond by a β(2-1) glycosidic link and typically have a terminal glucose. Inulin can be extracted from natural source. At this research, inulin’s extraction from dahlia root produces yield of inulin 3.99% and onion (Allium cepa) with yield of inulin 0.2%. Extract of inulin from dahlia roots has 3.9% reduce sugar, 7.0% cold water solubility, 1:1.4 water binding capacity and result of TLC analysis shows retention time Rf 0.50. Extract of inulin from onion has 2.5% reduce sugar, 10.5% cold water solubility, 1:1.1 water binding capacity and result of TLC analysis shows Rf 0.49. Extract of inulin at concentration 437.8 ppm both inulin from dahlia root and onion are able to influent Lactobacillus casei strain Bio 251 there are 52.6% and 48.1%. Synbiotic that containing extract of inulin, both inulin from dahlia root and from onion with minimum concentration 434.8 ppm can be inhibited Salmonella thypi that is one of bacteria causes diarrhea which values 94.6% and 91.4%, respectively.